FAKTOR-FAKTOR FASILITAS UMUM YANG DAPAT MEMBERIKAN KEPUASAN PENGHUNI PADA PERUMAHAN JEULINGKE RESIDENCE - Ahmad Y Agara; Sugiarto Sugiarto; Taufiq Saidi (Prodi Magister Teknik Sipil Unsyiah, 2020)
Public facilities are part of residential area that is provided by developer for the public interest. The public facilities available at Jeulingke Residence such as road, sanitation, drainage, clean water, and electric network. Based on the Republic of Indonesia Law Number 1 of 2011, and Minister of Public Housing Regulation Number 22 / PERMEN / M / 2008, Jeulingke Residence housing still has inadequate public facilities such as worship place, green area, and waste. The purpose this research to identify indicators of public facilities that provide satisfaction for residents of Jeulingke Residence, and identify dominant factors of public facilities that can provide satisfaction for residents of Jeulingke Residence. Respondents in this study were owners at Jeulingke Residence. The sample in this study was 150 people. The sampling technique used was proportionate stratified random sampling. The factors evaluated were infrastructure, facilities, and public utilities. Data processing used validity test, and reliability test, while data analysis used descriptive analysis and factor analysis of Principle Component Analysis (PCA). The results showed that the factors of public facilities that could provide satisfaction for residents at Jeulingke Residence were infrastructure and facilities. The dominant factor of public facilities that gives satisfaction to residents at Jeulingke Residence is infrastructure with a variance of 68.942%. Indicators of infrastructure are road condition, drainage condition, sanitation condition, clean water condition, and electric network condition.